Urinary incontinence in children in Cipto Mangunkusumo Hospital, Jakarta: a serial case report - Taralan Tambunan (Indonesian Pediatric Society, 2001)
Urinary incontinence in children is a complex problem of varying causes. Most children brought to physician for evaluation of difficulties with urinary control will have single or diurnal enuresis, or will be experiencing urgency associated with functional or organic incontinence. To find out the magnitude of urinary incontinence problems in Child Health Department Cipto Mangunkusumo Hospital Jakarta, we retrospectively looked at medical report of such cases between the years of 1989-2001. During eleven years there were 20 cases, consisted of 10 males and 10 females, aged ranged between 3 months up to 16 years. Nineteen children showed significant bacteriuria defined as a urinary tract infection. Ten children were diagnosed as having neurogenic bladder, all had spinal lesions; 7 children had spinal dysraphyism while 3 others had osteolityc lesions in vertebrae due to malignancy. Non neurogenic bladder was defined in 6 children, while in other 4 children we defined that urinary incontinence was caused by anatomical abnormalities. Vesico-ureteral reflux in various degree were found in 9 children, while 11 out of 20 (55%) cases were experiencing chronic renal failure on their first visit. Although the annual incidence of urinary incontinence is low, these difficult cases causing many problems. Breakthrough infection was almost unpreventable and in most cases had progressed to renal failure. Many factors such as invasive procedures and prolonged treatment causing fear and frustration to the patients and their parents leading to poor compliance and lost to follow up. In summary we can conclude that urinary incontinence in children is a complex problem include medically, economically, and socially, not only for the patient and their parents, but also for medical profession.